Upper Midwest freight corridor study - Gupta, Jiwan; Kawamura, Kazuya; Wittwer, Ernie F.; McNeil, Sue; Vonderembse, Mark; Lindquist, Peter; Bittner, Jason; Adams, Teresa M.; Gordon, Travis J. (Midwest Regional University Transportation Center, 2005)
This study was undertaken in order to establish a regional approach to improving freight transportation through the Upper Midwest corridor. Improving freight flows through the region can improve reliability and enhance competitiveness. This study examines several aspects of regional freight transportation including, capacity, performance measures, administrative issues, demand/usage and best practices. The project was funded by, six states in the region, through their Departments of Transportation, have contributed to a pooled fund to finance the majority of the work. These states include Illinois, Indiana, Iowa, Minnesota, Ohio, and Wisconsin.
233 p.
Keywords: Travel demand; Trucking; Airport capacity; Railroads; Freight transportation; Highway capacity; Reliability; Highways; Water transportation; Transportation corridors; State departments of transportation; Regional transportation